2013
DOI: 10.1007/s00134-013-3163-x
|View full text |Cite
|
Sign up to set email alerts
|

Specific MAIT cell behaviour among innate-like T lymphocytes in critically ill patients with severe infections

Abstract: This large human study provides valuable information about MAIT cells in severe bacterial infections. The persistent depletion of MAIT cells is associated with the further development of ICU-acquired infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
156
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(171 citation statements)
references
References 36 publications
12
156
2
1
Order By: Relevance
“…The importance of MAIT cells in bacterial infection has been further confirmed in a large clinical study involving patients suffering from severe sepsis or septic shock [80]. A comparison of patients suffering from severe bacterial infections (n = 113), no infection (n = 36) or severe viral infections (n = 7), compared with healthy controls (n = 26) revealed that a marked decrease in circulating MAIT cells occurs early following bacterial infection.…”
Section: Antibacterial Activity Of Mait Cells In Vivo In Humansmentioning
confidence: 81%
“…The importance of MAIT cells in bacterial infection has been further confirmed in a large clinical study involving patients suffering from severe sepsis or septic shock [80]. A comparison of patients suffering from severe bacterial infections (n = 113), no infection (n = 36) or severe viral infections (n = 7), compared with healthy controls (n = 26) revealed that a marked decrease in circulating MAIT cells occurs early following bacterial infection.…”
Section: Antibacterial Activity Of Mait Cells In Vivo In Humansmentioning
confidence: 81%
“…However, it has been shown that even if the HLA-DR expression has a positive slope to recover, the occurrence of a secondary infection once again induces a drop in HLA-DR expression. Whatever the mechanisms involved, it would appear to be relatively specific for MAIT cells, since the number of other innate-like lymphocytes, such as cd-T cells and NKT cells, did not change in ICU patients of Grimaldi et al [9].…”
mentioning
confidence: 87%
“…The major inputs of the Grimaldi et al [9] study are the observed reduction in MAIT cell number associated with prevalence of secondary infections in human beings which was not observed with other innate-like lymphocyte subsets, namely, the NKT and cd T cells. The authors confirmed the previously shown non-response of MAIT cells to Streptococcus spp., L. monocytogenes and virus infection.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, since the launch in 2013 of Intensive Care Medicine Experimental (ICMx), all preclinical research is transferred there. ICM may publish translational research if the reported data relate to clinical outcomes and provide a plausible biological basis for future clinical trials [1,2]. After this initial evaluation, about 60 % of papers are assigned to section editors who further appraise the manuscripts for originality, study design, degree of novelty, quality of reporting (writing, tables and figures), and statistical soundness, as well as competition with other manuscripts being considered for publication in the journal.…”
mentioning
confidence: 99%